Irritable bowel syndrome (IBS) among Lebanese adults: unidentified IBS and associated factors - Gabriella Yazbeck; Diana Malaeb; Hamid Shaaban; Abir Sarray El Dine; Souheil Hallit; Rabih Hallit (BMC, 2023)
Abstract Background Irritable bowel syndrome (IBS) is one of the most frequent functional gastrointestinal disorders, but the condition is still underdiagnosed. The high of rate of unidentified IBS by patients can be related to different factors. The aim of this study is to assess the rate of unidentified IBS among Lebanese adults and investigate the role of socio-demographic factors, anxiety, depression, insomnia and eating attitudes on IBS diagnosis. Methods A cross-sectional study was conducted among Lebanese adults older than 18 years between June 2022 and December 2022, using a self-reporting questionnaire distributed via social media. Results A total of 425 participants was enrolled in the study with around 184 (46.8%) having a possible unidentified IBS. Higher psychological distress (aOR = 1.07) and insomnia severity (aOR = 1.08) were significantly associated with higher odds of having possible unidentified IBS whereas a higher household crowding index (aOR = 0.67) was significantly associated with lower odds of having possible IBS. The correlation of eating attitudes with cigarette smoking (aOR = 1.33; p = .025; 95% CI 1.04; 1.70) and insomnia severity with cigarette smoking (aOR = .89; p = .023; 95% CI .80; .98) were significantly associated with the presence of possible IBS. In nonsmokers, higher psychological distress (aOR = 1.07) and insomnia severity (aOR = 1.10) were significantly associated with higher odds of having possible IBS. In smokers, higher BMI (aOR = .78) was significantly associated with lower odds of having possible IBS, whereas higher eating attitudes scores (more inappropriate eating) (aOR = 1.40) were significantly associated with higher odds of having possible IBS. Conclusion The study highlighted the implication of raising awareness about IBS among the Lebanese population to promote early diagnosis and minimize the rate of unidentified IBS by patients. Initiation of appropriate treatment plans, tailored symptomatic management approach, and diet programs should be highly encouraged.